Career Development and Employee’s Turnover Intention of Nepalese Banking Sector - Khatri , Shyam Kaji; Bastola , Tulashi Ram (Adhyayan Journal, 2026)
The research examined the career development and employee turnover intention of Nepalese banking sectors in Nepal. Data for the study were collected from the responses of 384 employees through a questionnaire survey on a five-point Likert scales. To achieve the research objective, descriptive and casual comparative research design have used. The research findings have based on quantitative data collected by distributing a questionnaire to the respondents. The total employees who are working in commercial banks inside the Kathmandu Valley is the population of this study. There was a positive correlation between Employee turnover intention, career development and job satisfaction, which was statistically significant at the 0.01 level. They have turnover intention not due to lack of scope for career growth but due to lack of job satisfaction with the majority of response in Nepalese banking industry. There was a significant mediating effect of job satisfaction in the relationship between career development and employee turnover intention. This study significantly provides insights to banking sectors to better understand how to reduce employee turnover by addressing organizational career growth of employees and make better decisions about employee’s career growth inside their organizations.